Disclosure and management of research findings in stem cell research and banking: policy statement. (May 2012) - Isasi, Rosario; Knoppers, Bartha M; Andrews, Peter W; Bredenoord, Annelien; Colman, Alan; Hin, Lee Eng; Hull, Sara; Kim, Ock-Joo; Lomax, Geoffrey; Morris, Clive; Sipp, Douglas; Stacey, Glyn; et al.
Prompted by an increased interest of both research participants and the patient advocacy community in obtaining information about research outcomes and on the use of their biological samples; the international community has begun to debate the emergence of an ethical 'duty' to return research results to participants. Furthermore, the use of new technologies (e.g., whole-genome and -exome sequencing) has revealed both genetic data and incidental findings with possible clinical significance. These technologies together with the proliferation of biorepositories, provide a compelling rationale for governments and scientific institutions to adopt prospective policies. Given the scarcity of policies in the context of stem cell research, a discussion on the scientific, ethical and legal implications of disclosing research results for research participants is needed. We present the International Stem Forum Ethics Working Party's Policy Statement and trust that it will stimulate debate and meet the concerns of researchers and research participants alike.